(untitled) (Clinics, 2016)
The purpose of this study was to evaluate the therapeutic options for diabetes treatment and their potential side effects, in addition to analyzing the risks and benefits of tight glycemic control in patients with diabetic kidney disease. For this review, a search was performed using several pre-defined keyword combinations and their equivalents: “diabetes kidney disease” and “renal failure” in combination with “diabetes treatment” and “oral antidiabetic drugs” or “oral hypoglycemic agents.” The search was performed in PubMed, Endocrine Abstracts and the Cochrane Library from January 1980 up to January 2015. Diabetes treatment in patients with diabetic kidney disease is challenging, in part because of progression of renal failure-related changes in insulin signaling, glucose transport and metabolism, favoring both hyperglycemic peaks and hypoglycemia. Additionally, the decline in renal function impairs the clearance and metabolism of antidiabetic agents and insulin, frequently requiring reassessment of prescriptions. The management of hyperglycemia in patients with diabetic kidney disease is even more difficult, requiring adjustment of antidiabetic agents and insulin doses. The health team responsible for the follow-up of these patients should be vigilant and prepared to make such changes; however, unfortunately, there are few guidelines addressing the nuances of the management of this specific population.